“Competencia mediática de los adultos mayores de la Iglesia Pentecostal Unida Internacional del Ecuador de la ciudad de Loja: retos para una inclusión digital y social, período mayo – agosto 2023” - Freire Elizalde, Bethy Esther (2024)
Nowadays, media skills are becoming more and more transcendental, because as time goes by, the media environment is becoming more and more digital and technological. But at the same time, there is a digital divide that impacts various groups of society, including the elderly. Among the objectives of this work of Curricular Integration, it was intended to determine through a diagnosis the level of media skills of older adults of the United Pentecostal International United Church of Ecuador (IPUIE) in the city of Loja, as well as the challenges they face for a digital and social inclusion, during the period May - August 2023. The methodological process followed for the fulfillment of the objectives is qualitative, which allowed us to collect, interpret, review in a systematic way and elaborate contrasts on these competencies, from a much broader perspective. An observation form with the six dimensions established by Ferrés and Picitelli (2012) was applied to 33 older adults of the IPUIE (Center and North), in order to know the level of media competence they possess. Similarly, two Pastors of the Church were interviewed, as well as experts on the object of study. The results of this research show that there is a significant digital divide, not only due to the lack of technological knowledge, but also due to socioeconomic barriers that prevent some older adults from accessing mobile devices, highlighting that most of them face limitations to manage in the digital environment. It is concluded that the lack of media literacy and the presence of technophobia are significant factors that limit the active participation of older adults in the digital society. Keywords: media competence; older adults; media literacy; digital inclusion; IPUIE (International United Pentecostal Church of Ecuador).